Workshop 1980 on Results and Experience, Companiganj Health Project, Noakhali : major conclusions and recommendations (Christian Commission for Development in Bangladesh, 1980)
Organized by the Christian Commission for Development in Bangladesh to evaluate the Project as a part of the Commission's community development program in Companiganj Thana, Noakhali District.